State and Federal Regulation of Corporate Takeovers: A View from the Demand Side - Jonathan R. Macey (Washington University Law Quarterly, 1991)
This Article argues that the key to understanding the complex regulatory environment in which the modern United States corporation is forced to operate lies in understanding the nature of the underlying groups who stand to win or lose as that environment changes. It is the thesis of this paper that, while corporate law has always reflected the outcome of a competitive struggle among rival groups for preferential treatment in the regulatory process, in recent years the stakes involved in this struggle have risen dramatically as a consequence of the costs and benefits imposed on these groups by the market for corporate control. Section I of this Article contains a discussion of the mechanics of interest group theory as that theory applies to corporate law. Section II illustrates the Article's thesis by examining three important sources of regulation in the market for corporate control: Congress, the SEC, and the states. First, I argue that Congress has responded to the increased political stakes associated with the modern market for corporate control by testing the regulatory waters. That testing triggered the dramatic stock market crash of October 1987, and caused Congress to conclude that the political costs of further regulation of the market for corporate control outweighed the gains. Next, the SEC's role in the regulation of corporate takeovers is considered. The SEC regulates the market for corporate control in a number of ways, some subtle and some quite overt. But all of the SEC's regulations of the market for corporate control respond to the preferences of a discrete interest group or groups. As with Congress and the SEC, state regulation of the corporate control market also is responsive to the demands of interest groups, but, as might be expected, the interest groups that dominate state legislatures not only differ from the interest groups that dominate the SEC, they also vary from state to state. Finally, in Section III, the Article considers the Supreme Court's role in fashioning the ground rules that govern the market for corporate control. This section shows that the Court has decided not to impede the rather obvious attempts by certain states to interfere with interstate commerce. I will argue that the only plausible explanation for the Court's inactivity lies in its mysterious desire to protect Congress from the political costs of regulating a field in which the political costs of regulation are greater than the benefits of such regulation.
Keywords: Consolidation & amp; merger of corporations; Political science; United States. Securities & amp; Exchange Commission